Timing of Closed Intubation in Recurrent Epiphoric Children - Javed Iqbal, Mumtaz Hussain, Abdul Rehman, Irfan Qayyum, Ali Zain-ul-Abidin, Najam Iqbal (Pakistan Journal of Ophthalmology, 2018)
Purpose: To determine the most appropriate time for closed intubation in recurrent epiphoric patients. Material and Methods: This was an interventional retrospective study which was conducted in the Eye Unit II, Institute of Ophthalmology, Mayo Hospital, Lahore, from January 2005 to January 2011. We performed closed intubation in 200 children up to four years of age, where syringing and probing failed twice at least. All patients were closed intubated with Crawford Silicon Tube under general anaesthesia. Epiphora and discharge was noted pre and post operatively at 1 month, 3 months and 6 months follow-up. Results: In this study there were 111 males and 89 females ranging from 1 to 4 years of age. In these 200 cases, 172 were relieved from epiphora and discharge while 28 patients had persistent epiphora. Failure as compared to age presentation observed during this period was as follows; 20 (71.4%) in 3-4 years of age; 6 (22.2%) in 2-3 years of age; 2 (7.4%) in 1 – 2 years of age. Conclusion: Closed intubation with silicon tube is an effective treatment modality for children of age between 1 to 4 years.